Social media portfolio (Facebook & Instagram) / Mohd Izwan Awang Sulong and Mohammad Asyraf Mastapa - Awang Sulong, Mohd Izwan; Mastapa, Mohammad Asyraf (2017)
Our product brand name is Doctor Kleenz. Doctor Kleenz is specializing in multipurpose cleaning spray product. It can be applied at almost every surface especially for car to get a very clean surface for example car dashboard, car door trim, car cushion or sofa at house etc. With an affordable price for such a high quality product like our Doctor Kleenz, we believe every each person especially car owner must have Doctor Kleenz as their main cleaning product.